"Rude and in Defiance of Authority": Arizona Anti-Mexican American Studies Legislation and the Discursive Positioning of the "Rude" Student of Color. (December 2022) - Howerton, Gloria
This article considers a style of civility discourse centered on perceived "rudeness" of youth, particularly youth of color (YOC) and its use as a political strategy that positions YOC as both uncivil and lacking agency. It is constructed as a racialized concept of rudeness that positions YOC as unreliable narrators and problem students whose voices can be dismissed when it comes to educational policy that directly impacts them. I refer to this discourse as "rudeness rhetoric." It takes on a key role in the (re)production of the school as a political site of white supremacist citizen production. I focus on Arizona politicians' mobilization of rudeness rhetoric as justification for legislation targeting Tucson Unified School District's (TUSD) Mexican American Studies (MAS) program for termination. I rely on triangulation of multiple sources and methods, including observation of meetings and the trial concerning the constitutionality of anti-MAS legislation, plaintiff evidence, documents and public statements by politicians, and online commentary concerning MAS. I find that, while politicians and the Arizona Department of Education engaged accusations that MAS promoted anti-white racism, they used rudeness rhetoric to frame the program as harmful, charging that it produced rude students based on protests politicians associated with MAS. Focusing on "rude" YOC allowed politicians to reframe legislative attacks on ethnic studies and move debate over MAS away from racial animus in the legislation. Rather than one explosive moment in which the rudeness rhetoric performed its political work, it snaked throughout multiple venues from political arenas to the courtroom to the media.